Parâmetros hematológicos e perfil bioquímico renal de cordeiros nascidos a termo e prematuros - Feitosa, F. L.F. [UNESP]; Alcindo, J. F. [UNESP]; Narciso, L. G. [UNESP]; Bovino, F. [UNESP]; De Souza, N. C. [UNESP]; Mendes, L. C.N. [UNESP]; Peiró, J. R. [UNESP]; Perri, S. H.V. [UNESP]; Avila, L. G. [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of the study was to evaluate hematologic parameters and renal biochemical profile of full-term and premature lambs from birth to 48 hours of life, and assess the effect of dexamethasone on such variables. Four experimental groups were formed: NDG (normal delivery group - lambs vaginally delivered, n = 15, average of 146-day gestation); NDEXG (normal delivery with dexamethasone group - lambs vaginally delivered whose mothers received 16 mg of dexamethasone at 141 days of gestation, n = 8, average of 143-day gestation); PRE (premature lambs born by cesarean section at 138 days of gestation, n = 10) and PREDEX (premature lambs born by cesarean section at 138 days gestation, whose mothers received 16 mg of dexamethasone two days before, n = 9). Mean values of cell volume and hemoglobin content decreased during the observation period of 48 hours in all groups, but within the physiologic limits for ovine species. There was significant variation in plasma concentration of total protein in all periods evaluated, with the lowest mean values in PRE group. The leukocyte count was significantly higher in PN group only in M24h. Throughout the observation period, only PN group showed differences between M24h and the other moments and PRE group showed the lowest values of neutrophils in M0h, M15min and M60min. Serum creatinine concentration was significantly higher in group PRE in M60min, M24h and M48h. In all groups, there was a decrease in M24 and M48. The evaluated parameters were affected by prematurity in sheep and dexamethasone had a positive effect on the survival rate of premature animals.
Hematologic parameters and renal biochemical profile in full-term and premature lambs